2005
DOI: 10.1088/0143-0807/26/3/016
|View full text |Cite
|
Sign up to set email alerts
|

Simple pendulum revisited

Abstract: We describe a 8085 microprocessor interface developed to make reliable time period measurements. The time period of each oscillation of a simple pendulum was measured using this interface. The variation of the time period with increasing oscillation was studied for the simple harmonic motion (SHM) and for large angle initial displacements (non-SHM). The results underlines the importance of the precautions which the students are asked to take while performing the pendulum experiment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
1
20
0
1
Order By: Relevance
“…If we demand an acceptable error of 0.5%, we find that the acceptable small-angle boundary would be 0.211 rad or 12 • . This boundary for the small-angle regime is in good agreement with earlier reports [24]. Interestingly, if we revisit Eq.…”
Section: Fourier Series Analysis Of the Nonlinear Pendulum Motionsupporting
confidence: 93%
See 1 more Smart Citation
“…If we demand an acceptable error of 0.5%, we find that the acceptable small-angle boundary would be 0.211 rad or 12 • . This boundary for the small-angle regime is in good agreement with earlier reports [24]. Interestingly, if we revisit Eq.…”
Section: Fourier Series Analysis Of the Nonlinear Pendulum Motionsupporting
confidence: 93%
“…In the case of SHM, for the initial condition θ(t = 0) = θ m andθ(t = 0) = 0, one can expect a 1 = θ m and b 1 = 0, thus enabling us to identify the small-angle condition. This method is unique when compared to those found in literature [24]. In order to study the mentioned transition, we have solved Eq.…”
Section: Fourier Series Analysis Of the Nonlinear Pendulum Motionmentioning
confidence: 99%
“…This phase difference is caused by a very small difference in frequency between the nonlinear models and the linear model, which adds up over many cycles. The small lag gets larger if the initial displacement from the equilibrium is made larger [18]. Fig.…”
Section: Dynamic System Responsementioning
confidence: 95%
“…More than a decade ago, the WA98 Collaboration has measured the elliptic flow v 2 of photons produced in P b + P b collisions at the beam energy of E beam = 158 AGeV [203], and it was found that the v 2 (γ incl ) of the low-transverse-momentum inclusive photons was about equal to the v 2 (π) of pions within the experimental uncertainties. This observation lead to the conclusion that either (Scenario a:) the contribution of the direct photons to the inclusive ones is negligible in comparison to the decay photons, i.e.…”
Section: Elliptic Flow Of Direct Photonsmentioning
confidence: 95%